Ornithophily in the Rhamnaceae: The pollination of the Chilean endemic Colletia ulicina - Medan, Diego (2005)
Colletia ulicina, an endemic species from the central region of Chile, displays red, tubular, scented, nectariferous flowers at the tip of its branches. Observations at two sites during two consecutive years indicate that the hummingbird Sephanoides sephaniodes (Trochilidae) visits the flowers on a regular basis. Captured hummingbirds had C. ulicina pollen loads on body parts matching the location of anthers and stigmas. The C. ulicina-S. sephaniodes interaction is well established (hummingbird visits were frequent, systematical, and occurred at different sites) although it lacks specificity (S. sephaniodes is a generalist hummingbird and C. ulicina has another, seasonally important pollinator, the even more generalist bumblebee Bombus dahlbomii). To the best of our knowledge this is the first documented report on bird pollination in the Rhamnaceae.